Bibliometric analysis of publications on the effect of animal production on climate change from past to present - Çelik, Şenol (Frontiers in Earth Science, 2024)
Bibliometrics and scientific mapping methods using R software, the biblioshiny web program, Scopus and VOSviewer were used to analyze the works of literature referenced and analyzed by the Web of Science during 1990-2023 in order to provide a thorough overview of the effect of animal production on climate change research from 1990 to 2023. A bibliometric analysis of 6558 publications that were published on the Web of Science database was done in order to determine which articles, authors, and journals were the most important. It also provided information on future study themes and gaps, as well as present topic trends. The most productive nations are China, the USA, and Australia; the most productive journals are Global Change Biology, The Science of the Total Environment, and Environmental Science and Pollution Research International. The analysis's findings show that, over the course of the study period, there was a noticeable rise in the number of research publications discussing how animal production is impacted by climate change, along with a steady expansion of the study area. The level of cooperation and research projects in this field among nations has increased, which has improved the caliber of publications over time. Important publications, writers, and journals in the area of how animal production affects climate change were also tallied. The problem of animal production and climate change will become significantly more dependent on new data, techniques, and technology.